2019
DOI: 10.3201/eid2510.190271
|View full text |Cite
|
Sign up to set email alerts
|

Global Epidemiology of Diphtheria, 2000–20171

Abstract: In 2017, a total of 8,819 cases of diphtheria were reported worldwide, the most since 2004. However, recent diphtheria epidemiology has not been well described. We analyzed incidence data and data from the literature to describe diphtheria epidemiology. World Health Organization surveillance data were 81% complete; completeness varied by region, indicating underreporting. As national diphtheria–tetanus–pertussis (DTP) 3 coverage increased, the proportion of case-patients <15 years of age decreased, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 11 publications
3
117
0
9
Order By: Relevance
“…years of age. It has been predicted that age of diphtheria case-patients could increase after introduction of DTP because a high proportion of older persons will be susceptible to the disease due to reduced circulation of bacteria, especially when no booster dose is provided (8). The 4 MLST types identified in this study (ST67, ST209, ST243, and ST244) were also identified in Thailand, Cambodia, the Philippines, and Binh Phuoc Province in Vietnam in the 2010s (4,9,10).…”
Section: Resultsmentioning
confidence: 99%
“…years of age. It has been predicted that age of diphtheria case-patients could increase after introduction of DTP because a high proportion of older persons will be susceptible to the disease due to reduced circulation of bacteria, especially when no booster dose is provided (8). The 4 MLST types identified in this study (ST67, ST209, ST243, and ST244) were also identified in Thailand, Cambodia, the Philippines, and Binh Phuoc Province in Vietnam in the 2010s (4,9,10).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, molecular tests detecting rpoB and tox gene should be considered for implementation in endemic/high-risk areas to decrease response time for DAT administration. [ 9 ] RpoB primer pairs: forward 5'-CGT TCG CAA AGA TTA CGG AAC CA-3’ and reverse 5'-CAC TCA GGC GTA CCA ATC AAC-3'; with 105bp product and tox gene - primer pairs: forward 5'-CTT TTC TTC GTA CCA CGG GAC TAA-3’ and reverse 5'-CTA TAA AAC CCT TTC CAA TCA TCG TC-3'; with 226bp product. [ 10 ] Briefly the PCR protocol includes, initial denaturation at 95°C for 10 min, followed by 45 cycles of 95°C for 15 s, and 60°C for 30 s for combined annealing and extension.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there are regions of endemicity for both diphtheria and pertussis, and factors such as age and vaccination status influence prevalence. Currently, in industrialized countries with high vaccination coverage, the incidence of these infections is relatively low, though it appears to be increasing [ 37 , 38 ]. In the case of diphtheria, DT is responsible for the clinical manifestations of disease, though several additional toxins, including adenylate cyclase and tracheal cytotoxin, are also involved in diphtheria disease.…”
Section: Toxin Detection In Infrequently Isolated Bacteriamentioning
confidence: 99%